“The Mnemosyne Atlas”: non finito in the history of art - Toropygina, Marina Yu. (Actual Problems of Theory and History of Art, 2012)
“The Mnemosyne Atlas” is Aby Warburg’s last project. This collection of Antiquity’s Pathosformel was designed to create Denkraum – a zone for reasoning, a space for thought one requires when confronting the magic world of images. Working mainly with visual evidence, Warburg transcends the limits of academic textual discourse. This unfinished project is valuable precisely because of its non finito – the essential nature of this art history masterpiece as an open work.
Keywords: Aby Warburg; “Mnemosyne Atlas”; Pathosformel; iconology; image and text; academic discourse; art history